(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
A compound sentence contains two or more independent clauses joined by coordinating conjunctions (for, and, nor, but, or, yet, so), semicolons, or conjunctive adverbs (however, therefore, moreover). Each clause can stand alone as a sentence. Key points include using a comma before coordinating conjunctions, semicolons for closely related clauses, and proper punctuation to avoid comma splices and run-on sentences. Varying sentence structures, maintaining clarity, and practicing correct punctuation are essential for mastering compound sentences, enhancing writing clarity and complexity in various contexts.